The Theme of Dialogue in the H. G. Gadamer’s Hermeneutical Philosophy - Gutauskas, Mintautas (Problemos, 2004)
The article analyzes the dialogue problem in the H. G. Gadamer’s hermeneutical philosophy. As primary point of the problem spreading is presented the interpretation construction of dialog between author and interpreter in F. D. Schleiermacher’s hermeneutic. The similarity between interpretation and the dialog is presented from the side of interpretation productivity and creation of new meanings. This is based on analysis of the dialogue as fusion of horizons and the experience of other being and reciprocal understanding in the communication. Finally, the article explains how incorporation of the theme of the dialog changes the conception of interpretation, its purpose, aim and method.